Reflecting Translanguaging in Classroom Practices: A Case Study - Magdalena Kartikasari Tandy Rerung (Universitas Bunda Mulia, 2018)
Strategies comes from Greek word “strategia” which means the art of planning and directing. Regarding to language learning, a strategy is used to achieve their goal depends on the skill they obtain. Specifically speaking skill is one of the productive skills that can be a challenging thing for university students who majored in English. Besides vocabulary, other element that support their language production is motivation. Avoiding in using Bahasa Indonesia can make them unmotivated sometimes. If this is the case, therefore the students might be passive learners in the classroom. Translanguaging is a strategy in language learning that can motivate students keep learning the language by combining their first language with the foreign one. The following case study is intended to observe how do students use translanguaging. The study was a class observation involving four students majored in English Language and Culture Program at Bunda Mulia University. They were in fourth semester and enrolling in the Listening and Speaking Class. Apparently the result shows that students who use their first language in the speaking task help them in delivering information and telling stories.Keywords: translanguaging strategies, speaking skill, language learning